Nature of Precipitation Resulted from Intravenous Drugs Incompatibility - Suci Hanifah; Patrick A. Ball; Ross A. Kennedy (Bumi Publikasi Nusantara, 2025)
In critical care, the co-administration of intravenous drugs often leads to physical incompatibilities, resulting in harmful precipitates. This study evaluated the nature of drug-induced precipitation in terms of size, shape, and quantity. Twelve drugs previously reported to be incompatible were tested with infusion fluids. Particle detection was conducted using an Olympus CX41 microscope with a 1 µm detection limit, enhanced by darkfield microscopy for better sensitivity. Particle size was analyzed using Feret’s diameter via the Optilab imaging system. Precipitates ranged from 5–150 µm, with smaller particles (<10 µm) seen in furosemide and subvisible particles (10–50 µm) in cefotaxime, chloramphenicol, and paracetamol. Visible particles were noted in acyclovir, ampicillin, meropenem, phenobarbital, and phenytoin. Most macro-precipitates were acicular, while micro-precipitates tended to be irregular. Particle counts ranged from 80 to 2,000 particles/mL. The findings highlight the clinical risk of particulate contamination due to drug incompatibilities, emphasizing the need for careful medication management.